2007
DOI: 10.1037/0022-3514.92.6.1006
|View full text |Cite
|
Sign up to set email alerts
|

Across the thin blue line: Police officers and racial bias in the decision to shoot.

Abstract: Police officers were compared with community members in terms of the speed and accuracy with which they made simulated decisions to shoot (or not shoot) Black and White targets. Both samples exhibited robust racial bias in response speed. Officers outperformed community members on a number of measures, including overall speed and accuracy. Moreover, although community respondents set the decision criterion lower for Black targets than for White targets (indicating bias), police officers did not. The authors su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
528
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(580 citation statements)
references
References 43 publications
45
528
7
Order By: Relevance
“…Eberhardt, Goff, Purdie, and Davies (2004) showed that priming police officers with crime-related words increased the attention they directed to Black faces relative to White faces. Correll et al (2007) conceptually replicated that result but then demonstrated that trained police officers were less likely to exhibit racial bias in a simulated shooting context than were community members-i.e., that implicit associations notwithstanding, behaviors toward members of stigmatized groups that are deliberate and explicitly executed may, through self-monitoring and/or training, prove to be relatively unbiased by such associations.…”
Section: Stereotyping and Prejudicesupporting
confidence: 50%
“…Eberhardt, Goff, Purdie, and Davies (2004) showed that priming police officers with crime-related words increased the attention they directed to Black faces relative to White faces. Correll et al (2007) conceptually replicated that result but then demonstrated that trained police officers were less likely to exhibit racial bias in a simulated shooting context than were community members-i.e., that implicit associations notwithstanding, behaviors toward members of stigmatized groups that are deliberate and explicitly executed may, through self-monitoring and/or training, prove to be relatively unbiased by such associations.…”
Section: Stereotyping and Prejudicesupporting
confidence: 50%
“…The main independent variable in Correll and colleagues studies was the skin colour of the target, either Black or White. Crucially, they did not constantly found a race-based discriminatory bias, which would consist in more hits and false alarms for Black targets (Correll, Park, Judd, & Wittenbrink, 2002;Correll, Urland, & Ito, 2006;Correll, Park, Judd, Wittenbrink, Sadler, & Keesee, 2007;however, Correll, Park, Judd, & Wittenbrink, 2007, using a strong priming procedure, and more recently, Correll, Wittenbrink Park, Judd, & Goyle, 2011, and Ma & Racism in soccer? 15 Correll, 2011 did find such discriminatory bias).…”
Section: Discussionmentioning
confidence: 99%
“…Shooter-bias, too, has been replicated with multiple, large samples of police officers (Correll et al, 2007; see also Peruche & Plant, 2006).…”
Section: Racial Bias In Policing: An Illustrative Casementioning
confidence: 99%